Exploiting the Fracture in Metal‐Organic Frameworks: A General Strategy for Bifunctional Atom‐Precise Nanocluster/ZIF‐8(300 °C) Composites. Issue 17 (20th March 2022) - Yun, Yapei; Fang, Yaping; Fu, Wengang; Du, Wenjun; Zhu, Yanan; Sheng, Hongting; Astruc, Didier; Zhu, Manzhou
Abstract: Atom‐precise nanoclusters‐metal‐organic framework (APNC/MOF) composites, as bifunctional material with well‐defined structures, have attracted considerable attention in recent years. Despite the progress made to date, there is an urgent need to develop a generic and scalable approach for all APNCs. Herein, the authors present the Exploiting Fracture Strategy (EFS) and successfully construct a super‐stable bifunctional APNC/ZIF‐8(300 °C) composite overcoming the limitations of previous strategies in selecting APNCs. The EFS utilizes the fracture of ZnN in ZIF‐8 after annealing at 300 °C. This method is suitable for all kinds of S/P protected APNCs with different sizes, including uncharged clusters Au1 Ag39, Ag40, negatively charged Au12 Ag32, positively charged Ag46 Au24, Au4 Cu4 and P‐ligand‐protected Pd3 Cl. Importantly, the generated APNC/MOF show significantly improved performances, for example, the activities of Au12 Ag32 /ZIF‐8(300°C), Au4 Cu4 /ZIF‐8(300°C), and Au1 Ag39 /ZIF‐8(300°C) in the corresponding reactions are higher than those of Au12 Ag32, Au4 Cu4, and Au1 Ag39, respectively. In particular, Au12 Ag32 /ZIF‐8(300 °C) shows higher activity than Au12 Ag32 @ZIF‐8. Therefore, this work offers guidance for the design of bifunctional APNC/MOF composites with excellent optimization of properties and opens up new horizons for future related nanomaterial studies and nanocatalyst designs. Abstract : A stable and efficient APNC/ZIF‐8(300 °C) catalyst is synthesized by the Exploiting Fracture Strategy. This strategy is suitable for all kinds of S/P‐protected atomic‐precise nanoclusters, and it overcomes the limitations of previous strategies in selecting nanoclusters. Furthermore, APNC/ZIF‐8(300 °C) composites have excellent catalytic properties in carboxylation of terminal alkynes, oxidation coupling of amines, and nitrophenol reduction.